SARS-CoV-2 Membrane Glycoprotein M Triggers Apoptosis With the Assistance of Nucleocapsid Protein N in Cells - Ren, Yujie; Wang, An; Fang, Yuan; Shu, Ting; Wu, Di; Wang, Chong; Huang, Muhan; Min, Juan; Jin, Liang; Zhou, Wei; Qiu, Yang; Zhou, Xi (Frontiers in Cellular and Infection Microbiology, 2021)
The pandemic of COVID-19 by SARS-CoV-2 has become a global disaster. However, we still don’t know how specific SARS-CoV-2-encoded proteins contribute to viral pathogenicity. We found that SARS-CoV-2-encoded membrane glycoprotein M could induce caspase-dependent apoptosis via interacting with PDK1 and inhibiting the activation of PDK1-PKB/Akt signaling. Our investigation further revealed that SARS-CoV-2-encoded nucleocapsid protein N could specifically enhance the M-induced apoptosis via interacting with both M and PDK1, therefore strengthening M-mediated attenuation of PDK1-PKB/Akt interaction. Furthermore, when the M-N interaction was disrupted via certain rationally designed peptides, the PDK1-PKB/Akt signaling was restored, and the boosting activity of N on the M-triggered apoptosis was abolished. Overall, our findings uncovered a novel mechanism by which SARS-CoV-2-encoded M triggers apoptosis with the assistance of N, which expands our understanding of the two key proteins of SARS-CoV-2 and sheds light on the pathogenicity of this life-threatening virus.